Consumer preferences for rice in East Africa - Twine, Edgar E.; Ndindeng, S.A.; Mujawamariya, G.; Adur-Okello; Kilongosi, C. (Emerald Publishing Limited, 2023)
Purpose – Improving the competitiveness of East Africa’s rice industries necessitates increased and viable production of rice of the quality desired by consumers. This paper aims to understand consumer preferences for rice quality attributes in Uganda and Kenya to inform the countries’ rice breeding programs and value chain development interventions. Design/methodology/approach – Rice samples are obtained from retail markets in various districts/ counties across the two countries. The samples are analyzed in a grain quality laboratory for the rice’s physicochemical characteristics and the resulting data are used to non-parametrically estimate hedonic price functions. District/county dummies are included to account for potential heterogeneity in consumer preferences. Findings – Ugandan consumers are willing to pay a price premium for rice with a relatively high proportion of intact grains, but the consumers discount chalkiness. Kenyan consumers discount high amylose content and impurities. There is evidence of heterogeneity in consumer preferences for rice in Mbale, Butaleja and Arua districts of Uganda and in Kericho and Busia counties of Kenya. Originality/value – The study makes a novel contribution to the literature on consumer preferences for rice in East Africa by applying a hedonic pricing model to the data generated from a laboratory analysis of the physicochemical characteristics of rice samples obtained from the market. Rather than base our analysis on consumers’ subjective sensory assessment of the quality characteristics of rice, standard laboratory methods are used to generate the data, which enables a more objective assessment of the relationship between market prices and the quantities of attributes present in the rice samples.